Covid-19 pandemic and economic landscape in Malaysia: a new crisis and norms - Sidah Idris; Jaratin Lily; Andi Tamsang Andi Kele; Jennifer Chan Kim Lian (BP Services, 2020)
The outbreak of the COVID-19 pandemic has brought a severe negative impact on the country’s economic and social life. The COVID-19 pandemic is regarded as a new form of crisis and has resulted in numerous uncertainties and developed new norms. The paper analyses the COVID-19 pandemic in Malaysia in relation to the Movement of Control Order (MCO) and the effects and changes in business and economic landscape as well as policy responses. It examines the five phases of MCO, and measures undertaken in each phase based on secondary data from various sources. It also analyses the policy responses of the Malaysian government during the COVID-19 pandemic; the new norms are discussed, too.